2022
DOI: 10.1016/j.jcot.2021.101720
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage arthroplasty for septic arthritis of the hip and knee: A systematic review on infection control and clinical functional outcomes

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…With femoral head osteomyelitis upon diagnosis and severe acetabular erosions, her infection would have been difficult to eradicate with irrigation and debridement alone. In this setting, a two-stage procedure can be performed with a temporary Girdlestone procedure or antibiotic spacer implantation [ 21 ]. Two-staged arthroplasty in the setting of late-stage septic hip arthritis allows for high rates of infection control and typically provides good to excellent functional outcomes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With femoral head osteomyelitis upon diagnosis and severe acetabular erosions, her infection would have been difficult to eradicate with irrigation and debridement alone. In this setting, a two-stage procedure can be performed with a temporary Girdlestone procedure or antibiotic spacer implantation [ 21 ]. Two-staged arthroplasty in the setting of late-stage septic hip arthritis allows for high rates of infection control and typically provides good to excellent functional outcomes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, a two-stage procedure can be performed with a temporary Girdlestone procedure or antibiotic spacer implantation [ 21 ]. Two-staged arthroplasty in the setting of late-stage septic hip arthritis allows for high rates of infection control and typically provides good to excellent functional outcomes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Native Joint Septic Arthritis Russo et al performed a systematic review on 2-stage exchange for native septic arthritis of the hip and knee. Using 21 studies comprising 435 procedures, the authors found an eradication rate of 93.3% at mean follow-up of 53.7 months 77 . Bettencourt et al analyzed 215 patients with a history of septic arthritis of the native knee who underwent TKA.…”
Section: Handmentioning
confidence: 99%
“…Treatment of acute bacterial arthritis consists of surgical intervention and antibiotic therapy (Goldberg and Sexton, 2022;Balato et al, 2021;Lum et al, 2018;Ross, 2017;Mathews et al, 2010;Rutz and Brunner, 2009). Surgical modalities range from arthroscopic or open debridement to (staged) total hip arthroplasty (THA) and (modified) Girdlestone procedures, using a variety of anatomical approaches (Balato et al, 2021;D'Angelo et al, 2021;Russo et al, 2021;Davis and Zamora, 2020;Lum et al, 2018;Rutz and Brunner, 2009).…”
Section: Introductionmentioning
confidence: 99%